Effects of nano-encapsulated curcumin-chrysin on telomerase, MMPs and TIMPs gene expression in mouse B16F10 melanoma tumour model. (5th November 2018) - Tavakoli, Fatemeh; Jahanban-Esfahlan, Rana; Seidi, Khaled; Jabbari, Masoumeh; Behzadi, Ramezan; Pilehvar-Soltanahmadi, Younes; Zarghami, Nosratollah
Abstract: Due to the high rate of drug resistance among malignant melanoma cases, it seems necessary to introduce an efficient pharmaceutical approach to melanoma treatment. For this purpose, Curcumin (Cur) and Chrysin (Chr), two natural anti-cancers, were co-encapsulated in PLGA-PEG nanoparticles (NPs), characterized by DLS, FTIR and FE-SEM and investigated for their effects on MMPs, TIMPs and TERT genes expression in C57B16 mice bearing B16F10 melanoma tumours. The results showed that the expression of MMP-9, MMP-2 and TERT genes were significantly decreased in all treated groups compared to the control. This reduction had the highest amount in CurChr NPs group and then CurChr group for each three genes. Likewise, the expression of TIMP-1 and TIMP-2 genes was significantly increased in all treated groups, compared to the control. Combination groups showed the highest rise in expression of these two genes and the observed increase was greater in nano groups. Moreover, the highest melanoma tumour growth inhibition was detected for CurChr NPs, followed by CurChr = Cur NPs > Cur > Chr NP > Chr. Overall, it is speculated that the nano-combination of Cur and Chr into polymeric NPs with a one-step fabricated co-delivery system may be a promising and convenient approach to improve their efficiency in melanoma cancer therapy.